Rotational interval exchange transformations - Teplinsky, A. (Ukrains’kyi Matematychnyi Zhurnal, 2024)
UDC 517.5 We show the equivalence of two possible definitions of a rotational interval exchange transformation: by the first definition, it is the first return map for a circle rotation onto a union of finitely many circle arcs and, by the second definition, it is an interval exchange with a scheme (in the sense of interval rearrangement ensembles) whose dual is also an interval exchange scheme.